BIOLOGY - Campbell, Neil A.; Reece, Jane B.; Urry, Lisa A.; Cain, Michael L.; Wasserman, Steven A.; Minorsky, Peter V.; Jackson, Robert B. (Pearson Benjamin Cummings, 2008)
eil Campbell and Jane Reece's BIOLOGY is the unsurpassed leader in introductory biology. The text's hallmark values-accuracy, currency, and passion for teaching and learning-have made Campbell/Reece the most successful book for students and instructors for seven consecutive editions. Campbell/Reece is used in 2 out of 3 introductory biology courses for majors. More than 6 million students have benefitted from BIOLOGY'sclear explanations, carefully crafted artwork, and student-friendly narrative style. 65 percent of all doctors and biological scientists in the United States under the age of 40 began their study of biology with this book. For the Eighth Edition, new coauthors have joined with those from previous editions to infuse this proven text with new ideas while upholding its hallmark values. Their collaboration has produced the authoritative introduction to biology, told with a unified voice and vision